Programação concorrente baseada em acordes para plataforma java - Sergio Vale e Pace (2009)
The most important mechanisms used to express parallelism and concurrency available in major modern programming languages are constructions with low level of abstraction, inadequate to the development of large scale concurrent systems. This makes the task of design, analyze, implement, test and debug concurrent systems to be quite difficult. The chord is a high level construction based in the processes algebra join-calculus, that enables to express the concurrent relationships declaratively, allowing to coordinate the interactions between parallel flows of execution implicitly. We propose a chord based concurrent programming library for the Java platform. Through this library we seek to allow the development of parallel and concurrent systems in a greater level of abstraction, in a simpler, more effective e less error prone way. It uses an implementation based on annotations and dynamic bytecode instrumentation that allows to adapt the syntax and semantic of the language, providing means to express chords in a natural way without compromising the standard java environment for development and execution.